2010
DOI: 10.1111/j.1600-0765.2009.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary microbial levels in relation to periodontal status and caries development

Abstract: This study showed that an inverse relationship exists between periodontitis and caries in terms of the clinical and bacteriological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 38 publications
1
33
1
6
Order By: Relevance
“…Measurement of the GI and GBI corroborated with some periodontal studies (Iwano et al 2010;Saygun et al 2011), which describe that some clinical alterations are identified only in the advanced stages of the disease, and in this stage, preventive measures are not effective. The increase in the GCF volume indicated an immune response as a result of the PI increase.…”
Section: Discussionsupporting
confidence: 67%
“…Measurement of the GI and GBI corroborated with some periodontal studies (Iwano et al 2010;Saygun et al 2011), which describe that some clinical alterations are identified only in the advanced stages of the disease, and in this stage, preventive measures are not effective. The increase in the GCF volume indicated an immune response as a result of the PI increase.…”
Section: Discussionsupporting
confidence: 67%
“…(Iwano et al 2010;Saravia et al, 2011;Takahashi e Nyvad, 2011). Um aumento destas espécies ocorre entre 6 e 12 semanas após a instalação de aparelhos ortodônticos (Sanpei et al, 2010).…”
Section: Resultsunclassified
“…Resultados recentes, de estudos clínicos com bráquetes metálicos convencionais e biologia molecular apontam para a multicolinização que ocorre após a instalação dos aparelhos ortodônticos, revelando a complexidade da interação das espécies na colonização da superfície dentária e do bráquete, in situ (Iwano et al, 2010;Jurela et al, 2013;Barker et al, 2013). corroborando com os resultados dos estudos que apontam as alterações da microbiota após instalação dos aparelhos ortodônticos em função da quebra do equilíbrio do meio (Marsh, 2006;Demling et al, 2009;Barker et al 2013).…”
Section: Discussionunclassified
See 2 more Smart Citations